Endoscopic removal and replacement of the same lumen-apposing metal stent for multiple endoscopic necrosectomy sessions - Gulati, Rishabh; Rustagi, Tarun (Endoscopy, 2020)
Background This study evaluated the feasibility, efficacy, and safety of removal and replacement of a lumen-apposing metal stent (LAMS) to facilitate direct endoscopic necrosectomy (DEN).Methods Endoscopic ultrasound-guided LAMS placement for walled-off necrosis (WON) was performed. During subsequent endoscopy, the LAMS was removed, DEN was performed, and the same LAMS was redeployed across the transmural tract.Results 140 LAMS were placed for drainage (43 pseudocysts, 97 WON) from 10/1/2016 to 11/15/2019, and 40 patients (mean age 43.9 [SD 15.4] years; 70 % males; mean WON size 10.9 [SD 4.9] × 8.7 [SD 3.8] cm) underwent removal and replacement of the same LAMS for multiple DEN sessions. LAMS was successfully replaced across the transmural tract during all 81 DEN sessions. Complete resolution was achieved after a median of 2 DEN sessions (range 1–7; mean 2.4 [SD 1.5]), with stent retrieval after a mean of 64.1 (SD 31.6) days after initial placement. No stent damage, tissue ingrowth, or major bleeding occurred.Conclusions Removal and replacement of LAMS during multiple necrosectomies is feasible, safe, and facilitates DEN.